A COMPARATIVE STUDY OF T-TUBE VERSUS ANTE GRADE STENTING OF CBD AFTER OPEN CBD EXPLORATION FOR CHOLEDOCHOLITHIASIS - HAFIZ HAMZA BILAL; IQBAL AZIZ; SYED HASAN HARRIS; SHAHLA PARVEEN (The Bioscan, 2025)
Background: Choledocholithiasis is the second most common complication of cholelithiasis1 and causes non- malignant biliary obstruction.2 Once CBD stones are confirmed, they were extracted out as early as possible to prevent complications. 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21 CBD stones can be removed by endoscopic retrograde cholangiopancreatography (ERCP), or surgically, by an open or laparoscopic method but Open exploration is the principal method practicing from 100 years. 5 After choledochotomy, it can further be managed either by primary closure of CBD, by T-tube drainage or by primary closure with biliary stent insertion. Aim: To compare the post-operative outcomes in patients of choledocholithiasis with or without cholelithiasis who underwent open CBD exploration followed by T-tube insertion or biliary stent placement. Study design: This was randomized comparative study conducted on 24 diagnosed patients of choledocholithiasis with or without cholelithiasis in the Department of Surgery, Ajmal Khan Tibbiya College, F/O Unani Medicine AMU, Aligarh during January 2020 to October 2022. Patients were divided in two groups (Group A and Group B), each having 12 patients. Methods: selected patients in the study were underwent CBD exploration for choledocholithiasis. out of which 12 patients in Group A underwent CBD exploration followed by T-tube placement and 12 patients in Group B underwent biliary stent insertion after open CBD exploration. Result: There were 22 females and 2 males out of 24 patients enrolled in the study. Mean operating time was significantly less in biliary stent group as compared with T-tube group (50.17+6.534 & 59.08+7.179, ‘p’=0.0043 and ‘t’=3.182). duration of post-operative hospital stay was less in group B as compared with group A (7.167+1.850 & 16.08+1.929 where ‘p’= 0.001 and ‘t’=11.56) which was statistically highly significant. wound infection was observed in 5 patients (41.6%) of T-tube group and 3 patients (25%) of biliary stent group. There were no post-operative complications in our study in both the groups. Conclusion: primary closure with biliary stent is better than T-tube placement after common bile duct exploration in terms of operating time, post-operative hospital- stay, post-operative complications, patient’s satisfaction, quality of life and early return to normal activity.